Virtual molecular docking study of some novel carboxamide series as new anti-tubercular agents - Abdullahi, Mustapha; Uzairu, Adamu; Shallangwa, Gideon Adamu; Arthur, David Ebuka; Umar, Bello Abdullahi; Ibrahim, Muhammad Tukur (European Journal of Chemistry, 2020)
A virtual docking simulation study was performed on thirty-five newly discovered compounds of N-(2-phenoxy) ethyl imidazo[1,2-a] pyridine-3-carboxamide (IPA), to explore their theoretical binding energy and pose with the active sites of the Mycobacterium tuberculosis target (DNA gyrase). The chemical structures of the compounds were drawn correctly with ChemDraw Ultra software, and then geometrically optimized at DFT level of theory with Spartan 14 software package. Consequently, the docking analysis was carried out using Molegro Virtual Docker (MVD). Five complexes (Complex 5, 24, 25, 33 and 35) with high binding energy were selected to examine their binding pose with the active sites of the protein. The docking results suggested a good MolDock score (≥ -90 kcal/mol) and Protein-Ligand ANT System (PLANTS) score (≥ -60 kcal/mol) which depicted that the compounds can efficiently bind with the active sites of the target. However, compound 5 has the best binding pose with the MolDock score of -140.476 kcal/mol which formed three hydrogen bond interactions with the Gln 538, Ala 531, and Ala 533 amino acid residues. This research gives a firsthand theoretical knowledge to improve the binding efficiency of these compounds with the target.